Synthesis and investigation of structural and optical properties of CdO: Ag nanoparticles of various concentrations - Suaad A. Muhammed; Nada K. Abbas (مجلة بغداد للعلوم)
This study discussed the effects of doping with silver (Ag) on the optical and structural properties of CdO nanoparticles at different concentrations 0, 1, 2, 3, 4, 5 wt% prepared by the precipitation method. The materials were annealed at 550˚C for 1 h. The structural, topographical, and optical properties were diagnosed by X-ray diffraction analysis, atomic force instrument, and visible and ultraviolet spectrometers. The results show that the average diameter of the grains depends on the percentage of added silver to the material, as the diameter decreased from 88.8 to 59.7 nm, and it was found that the roughness increased from 5.56 to 26.5. When studying the optical properties, it was noted that the energy gap was 2.53ev for the pure sample and decreased to 2.38 When 5% of silver concentration was added to cadmium oxide